(untitled) (Journal of Nobel Medical College, 2017)
Osteochondromas are most common benign bone tumor occurring at the metaphyseal region of long tubular bone but rarely seen at maxillofacial region with less than 100 cases of mandibular condyle osteochondromas reported in literature. This article reports a rare case of mandibular condyle osteochondroma with associated fracture in 32 years old female patient presenting with sudden onset of severe pain at right preauricular region following yawning. Journal of Nobel Medical College Volume 6, Number 1, Issue 10 (January-June, 2017), page: 83-85